Optimum Naso‐oropharyngeal Swab Procedure for COVID‐19: Step‐by‐Step Preparation and Technical Hints. (20th August 2020) - Coden, Elisa; Russo, Federico; Arosio, Alberto D.; Castelnuovo, Paolo; Karligkiotis, Apostolos; Volpi, Luca
Abstract : View Video S1